The optimality of multi-stage venture capital financing: An option-theoretic approach - Robert Dubil (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
For venture capital firms, facing undiversifiable risks, multi-staged financing is an optimal contract which offers significant risk reduction at a cost of only slightly lower potential return. The optimality does not depend on the presence of moral hazard and agency problems. Our theoretical model of multi-stage financing, largely based on Asian option pricing theory, allows us to compute the risk reduction ratio due to multi-staging. The return on a staged financing plan is equivalent to an exchange of a straight equity stake for that acquired through stochastic averaging over time. We compare standard deviation ratios for staged vs. up-front financings as well as across asset classes. We find that risk mitigation due to multi-staging is significant in and of itself and enough to markedly improve venture capital's risk-reward ratios relative to alternatives.
Keywords: 650